2007
DOI: 10.1073/pnas.0706984104
|View full text |Cite
|
Sign up to set email alerts
|

Identification of acyltransferases required for cutin biosynthesis and production of cutin with suberin-like monomers

Abstract: Cutin and suberin are the two major lipid-based polymers of plants. Cutin is the structural polymer of the epidermal cuticle, the waterproof layer covering primary aerial organs and which is often the structure first encountered by phytopathogens. Suberin contributes to the control of diffusion of water and solutes across internal root tissues and in periderms. The enzymes responsible for assembly of the cutin polymer are largely unknown. We have identified two Arabidopsis acyltransferases essential for cutin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
342
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(363 citation statements)
references
References 36 publications
12
342
1
3
Order By: Relevance
“…8). These results are consistent with similar observations on the Arabidopsis gpat4/gpat8 mutant lacking glycerol-3-phosphate acyltransferase (GPAT4 and GPAT8) activity, which is essential for cutin biosynthesis (Li et al, 2007). It has been reported that Ser esterases with cutinolytic activities were only expressed during initial contact between A. brassicicola conidia and cutin on host surfaces that did not contain wax (Fan and Kö ller, 1998), which also supports our observations.…”
Section: Discussionsupporting
confidence: 82%
“…8). These results are consistent with similar observations on the Arabidopsis gpat4/gpat8 mutant lacking glycerol-3-phosphate acyltransferase (GPAT4 and GPAT8) activity, which is essential for cutin biosynthesis (Li et al, 2007). It has been reported that Ser esterases with cutinolytic activities were only expressed during initial contact between A. brassicicola conidia and cutin on host surfaces that did not contain wax (Fan and Kö ller, 1998), which also supports our observations.…”
Section: Discussionsupporting
confidence: 82%
“…The enrichment in the 'suberin' GO term is in agreement with the upregulation in cork oak outer bark of the putative orthologs of wellknown Arabidopsis or potato enzymes with a key role in the biosynthesis of suberin (Table S6A). Specifically, we found upregulation in cork of putative orthologs to the Arabidopsis GPAT5, CYP86A1, CYP86B1 and AtHHT/ASFT, and of putative orthologs to the potato CYP86A33 and FHT Li et al 2007;Höfer et al 2008;Serra et al 2009Serra et al , 2010Compagnon et al 2009;Gou et al 2009;Molina et al 2009). Aside from suberin, phellem imperviousness has been attributed to the associated waxes, which in cork consist mainly of isoprenoids such as triterpenes and sterols (Castola et al 2005).…”
Section: Discussionmentioning
confidence: 85%
“…Li et al (O5) studied a double knock-out mutant gpat4/gpat8 affected in glycerol-3-phosphate acyltransferases (GPATs), and showed a strong reduction in cutin monomers and a steep increase in cuticle permeability. Overexpression of any of these acyltransferases in Arabidopsis increased up to 80% the content of specific C16 and/or C18 cutin monomers in leaves and stems [37]. These results identify the first acyltransferases involved in cutin synthesis.…”
Section: Sphingolipids Sterols Isoprenoidsmentioning
confidence: 67%